SUSTAINABILITY IN AGRIBUSINESS the impact of societal challenges. - Annosi, Maria Carmela; Appio, Francesco; Brunetta, Federica ([S.l.] : ROUTLEDGE, 2023)
Accomplishing sustainability in the agribusiness sector is a significant, yet time-sensitive, challenge, especially when balanced with the need to grow sufficient quantity and quality of food to keep the growing global population healthy. Through both quantitative and qualitative methods, this book explores the extent to which the agribusiness sector is already evolving to become sustainable and the ways in which innovation in the industry can help address sustainable development goals, particularly around zero hunger, gender equality, decent work, responsible consumption and production, and climate action. The contributors to this volume address the following key questions: What are the drivers and barriers for the agribusiness sector to become sustainable? Which business models best facilitate the implementation of sustainable goals? How can we measure the extent to which the agribusiness sector is becoming more sustainable? How can the agribusiness sector leverage recent technological advancements to achieve its sustainability goals? The analysis of the sustainability challenges for the sector ranges across various facets of the industry including employment, pre-production industries, agriculture, food processing, distribution, and trade. This book will be of significant interest to readers in agribusiness, innovation management, and sustainability.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Industries / Agribusiness; BUSINESS & ECONOMICS / Green Business; Agricultural industries -- Environmental aspects; Sustainable development